UNDERGRADUATE THESIS ANALYSIS OF MANAGEMENT OF BOROBUDUR TEMPLE AS TOURISM OBJECT AND CULTURAL PROPERTY (Case Study: Unit PT. Taman Wisata Candi Borobudur) - Robi'ah Nuraini (IPEM 15 UMY 98, 2015)
*98